Earth as Mother, Mother as Earth: Evolving Topographies of Body and Terra: An Inter-media Drawing Practice - Selkirk-Hanna, Alexandra (Auckland University of Technology, 2023)
This project offers a visual and aural means to re-understand our contemporary eco-political position through the lens of the queer, internal, pregnant and post-partum bodily landscape alongside Earth’s ecology and geology. This amalgam enables attunement to matters of care, interdependence and responsibility. The research is embodied in an inter-media drawing practice of digital, interactive environments, printmaking, sound and sculpture. The methods in inter-media drawing reveal a process of world-building that is synergetic with the multifarious realities of life and non-life on our planet.